Konsep Ulul Albab dalam Qs. Ali Imran Ayat 190-191 dan Implikasinya Terhadap Kecerdasan Moral Anak - Susi Setiawati; Eko Surbiantoro; Dinar Nur Inten (UNISBA Press, 2024)
Abstract. This research is motivated by various phenomena that occur today where children's behavior often does not comply with applicable norms. Therefore, it is necessary to train children's moral intelligence, so that they can develop good behavior and become perfect human beings. So the problem in this research is formulated as follows: (1) What is the perspective of the commentators regarding the concept of ulul albab contained in the QS. Ali Imran verses 190-191? (2) What are the views of educational experts regarding the concept of ulul albab as moral intelligence? (3) What are the essences contained in the QS. Ali Imran verses 190- 191? (4) How is the concept of ulul albab applied to the development of moral intelligence? The aim of this research is to find out